2012
DOI: 10.1177/1070496512447249
|View full text |Cite
|
Sign up to set email alerts
|

Community Forestry, Common Property, and Deforestation in Eight Mexican States

Abstract: Community management of forests for timber extraction has been widely implemented in Mexico. In this article, we investigate the relationship between property rights, community forestry, and deforestation over time. We conduct an econometric analysis of land use change at the municipality level in eight Mexican states that incorporates several variables commonly used in deforestation models plus variables on common property and community forestry. Our results show that both key explanatory variables, common pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…For both PML-only and PMI treatment plots, simple difference-in-difference regressions with control variables generate estimates that indicate reduced forest loss as a result of PSUR. These results are similar to other studies that do not address selection and collinearity in regression (e.g., Barsimantov and Kendall, 2012). The PSUR intervention in our study area is implemented in areas that already have lower background rates of deforestation as compared to non-program areas.…”
Section: Discussionsupporting
confidence: 90%
“…For both PML-only and PMI treatment plots, simple difference-in-difference regressions with control variables generate estimates that indicate reduced forest loss as a result of PSUR. These results are similar to other studies that do not address selection and collinearity in regression (e.g., Barsimantov and Kendall, 2012). The PSUR intervention in our study area is implemented in areas that already have lower background rates of deforestation as compared to non-program areas.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, the transfer of forest management authority from states to communities has been partial and disappointing, and local control over forest management appears to have more ecological than socioeconomic benefit. The trend in the Brazilian Amazonian, Cambodia, Mexico and Nepal shows that CF initiatives are reducing rural poverty while promoting the conservation and sustainable use of forests despite some challenges (Barsimantov & Kendall, 2012;Chhetri et al, 2012;Hajjar et al, 2011;Lambrick et al, 2014;Pokharel, 2012). The general trends in CF prove that CF can contribute to the wellbeing of local people if implementation challenges are revolved.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is hardly the case that every ejido is sustainable, ejidos overall can play an important role in conservation efforts. Indeed, multiple studies across México, and specifically in the Yucatán peninsula, have shown that ejidos can contribute to landscape conservation (Barsimantov & Kendall, ; DiGiano, Ellis, & Keys, ; Ellis, Romero Montero, & Hernández Gómez, ). In particular, community forest management for timber extraction has played a pivotal role in maintaining forest cover and biodiversity conservation (Ellis, Romero Montero, & Hernández Gómez, ; Ortega‐Huerta & Kral, ).…”
Section: Introductionmentioning
confidence: 99%